Site factors and stand conditions associated with Persian oak decline in Zagros mountain forests - Hosseini, Ahmad; Hosseini, Seyed M.; Linares, Juan C. (Forest Systems, 2017)
Aim of study: Drought and stand structure are major and interconnected drivers of forest dynamics. Water shortage and tree-to-tree competition may interact under the current climate change scenario, increasing tree mortality. In this study, we aimed to investigate climate trends, site and stand structure effects on tree mortality, with the main hypothesis that drought-induced mortality is higher as competition increases.Area of study: Persian oak forests from Zagros Range, western Iran.Material and Methods: We split the study area into 20 topographical units (TUs), based on aspect, slope and elevation. In each TU, three 0.1 ha plots were established to quantify site and stand characteristics, namely the diameter of all trees and shrubs, stand density and basal area, canopy dieback and mortality. In addition, soil profiles were analyzed to obtain physical and chemical soil properties. Six transects 100 m length were established per TU to measure tree-to-tree competition for alive and dead trees.Main Results: The highest mortality rates and crown dieback were found at higher elevations and southern and western aspects. Our findings confirm increasing rates of tree mortality in stands with higher tree density and shallow soils. As regard links between climate change and forest decline, our results suggest that changing forest structure may have a significant impact on dust emission.Research highlights: Despite severe dry years occurred recently the study area, they are not significantly different than those recorded in the past. Stand structure appears as a modulating factor of climate change effects, linked to competition-related tree vulnerability to drought.